DETEKSI CEPAT GEN INVA PADA SALMONELLA ATCC DENGAN LOOP-MEDIATED ISOTHERMAL AMPLIFICATION (LAMP) - Soni Muhsinin; Rahma Ziska; Maria Martina Sulastri (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Salmonella spp. is a bacterium that causes typhoid salmonellosis (typhoid fever). These bacteria enter through the oral route, usually by contaminating food and drinks. Salmonella spp. has an invA gene that causes pathogenicity in humans. The culture method is used as a gold standard to detect Salmonella spp. However, this method requires infrastructure and is laborious. The purpose of this study is to develop detection of Salmonella spp. using the Loop-Mediated Isothermal Amplification (LAMP) method. The stages of the study began with the primary design of LAMP, Salmonella ATCC culture, DNA Isolation of Salmonella ATCC culture, and Salmonella ATCC LAMP Optimization. Primary LAMP that has been designed consists of three pairs. Salmonella ATCC DNA that has been isolated has a concentration of 4,5 ng/ul. The LAMP method shows positive results in detecting the InvA gene in Salmonella ATCC. Positive results are indicated by fluorescence in Salmonella ATCC DNA samples, whereas the negative results are shown in the absence of fluorescence in nuclease free water. The conclusion from the research that has been done, LAMP method can detect InvA gene in Salmonella ATCC.